Effects of sepiolite and biochar on microbial diversity in acid red soil from southern China. Issue 9 (21st October 2019) - Qin, Xu; Huang, Qingqing; Liu, Yiyun; Zhao, Lijie; Xu, Yingming; Liu, Yetong
ABSTRACT: Sepiolite and biochar can immobilize heavy metals and organic pollutants in soil effectively, but their impact on the soil microbial community and diversity is still unclear. High-throughput Illumina MiSeq method was used to study the effects of sepiolite and biochar on the diversity of microbial communities in acid red soil amended with cadmium and atrazine. A total of 47, 472 microbiological Operational Taxonomic Units (OTUs) were found in all the treated soil samples. Sepiolite and biochar enriched the diversity of soil microbes at different classification levels and OTUs, but the effect of biochar was stronger than that of sepiolite. A Venn diagram showed that compared with other treatments, adding 2% biochar could promote the growth of specific microbes, which is better than the case for 5% biochar. The heat map of species abundance cluster showed that the dominant microbes in soil were different for different treatment doses of sepiolite and biochar. Among all the soil treatments, the top ten dominant bacterial phyla (from high to low dominance) were: Actinobacteria, Proteobacteria, Firmicutes, Bacteroidetes, Acidobacteria, Gemmatimonadetes, Chloroflexi, Planctomycetes, Cyanobacteria, and Verrucomicrobia. The addition of sepiolite and biochar promoted the restoration of the microbial community diversity in contaminated soil.